Comparative Anthropometric Profile in athlete students and non athlete ones. - Georgina Jiménez Estrada; Gema Matienzo González Carvajal; Juan José Apollinaire Pennini; María Teresa Martínez Barroso; Marta Gómez Arcila; Hilda Carmouce Cairo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: Anthropometric is applied in the evaluation of the nutritional risks especially in children. Objective: To determine the anthropometric profile athlete students and non athlete ones belonging to 5th and 6th grade respectively from two primary schools in Cienfuegos Province. Method: A comparative study of a study group and a control group formed by 124 children. An evaluation was performed on weight, size, triceps skinfold, and branchial circumpherence using the Cuban weight scales for size, weight according to age, size for the age, triceps skinfold, and branchial circumpherence in regard to the age, as well as the Z score for weight and size. Results: In general terms, students in normal weight were predominant for a 63.6 per cent of them. The school specialized in sports showed the major number of students with low weight and the normal school had the overwight ones. High levels of malnutrition were found in the normal school, 20 per cent of overweight students and 9.1 per cent of undernourished students. Values for low size were found greater in in the school especialized in sports with 14.4 per cent. Conclusions: Anthropometric measurements in athlete students do not differ essencially from the non athlete ones.